Prioritising the Factors for Analysing Service Quality of 3PL: AHP Approach. (March 2017) - Gupta, Anchal; Singh, Rajesh K.; Suri, P.K.
Due to wide growth of digitalisation and globalisation, organisations need to serve customer demand with quality services, domestically as well as globally. Organisations always preferred to outsource their supply chain and logistics operations to third-party logistics (3PL) for the purpose of timely delivery and better service quality. This article aimed to find out the key parameters that affect the quality of services provided by 3PL to the organisations. Assets, processes and services are the three broader categories desired by organisations at the time of selection of best 3PL. The evaluation of parameters under these categories has been done by using Analytical Hierarchical Process (AHP) and the ranking of parameters may help the organisations to make the best decision regarding selection of best 3PL among all the available alternatives.